ANALYSIS OF IFN-γ CONCENTRATION IN WISTAR RAT BLOOD AFTER ORAL ADMINISTRATION OF STANDARDIZED GREEN TEA WATER EXTRACT - Djoko Agus Purwanto; Retno Pudji Rahayu; A. Toto Purnomo (Universitas Gadjah Mada, 2010)
Green tea and its polyphenols have been studied extensively as cancer chemopreventive agents in recent years. However, the mechanisms of action are still not clearly understood. Some researchers suggest that immune system plays important role to destroy cancer cells. Because of that reason, the present study was designed to analyse the effects of oral administration standardized green tea water extract on increasing of IFN-g blood concentration and to elucidate possible mechanisms involved in the inhibitory action of the cancer development. Two groups (male and female) of 5 rats have given p.o. administration 1.25% of standardized green tea water extract and got 300 mg of (-)-epigallocatechin gallate (EGCG)/kg body weight, while two groups others (male and female) were used as control. We found that IFN-g blood concentration on male and female Wistar rat are significantly increase with 13.11% and 17.59%, respectively (p<0.05) by ELISA method, whereas control had no increase. These results indicate that standardized green tea water extract has possibility to prevent and suppress cancer development through enhancing IFN-g expression and other immunosurveillance component.